(untitled) (Bangladesh Journal of Medical Microbiology, 2012)
This cross sectional study was done from January 2009 to June 2010 in Microbiology department of Dhaka Medical College, Dhaka to identify hookworm species and to compare different laboratory methods for diagnosis of hookworm infections. Among the 375 stool samples evaluated, 26 (6.93%) samples were positive for hookworms. Ankylostoma duodenale were 3 (11.50%) and Necator americanus were 23 (88.50%). Harada Mori culture was found as the most effective method for detection of hookworms. DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10821